82.9k views
4 votes
Question is from definite integral.

Question is from definite integral.-example-1

1 Answer

6 votes

Answer:

The value of the sum is:
$ (\pi)/(4) $.

Explanation:

Given:
$ \lim_(n \to \infty) \displaystyle \sum_(k = 1)^ {n} \bigg ( (n)/(n^2 + k^2) \bigg ).

Taking
$ n^2 $ common outside from the denominator, we have:


$ \bigg ( (n)/((n^2)(1 + ((k^2)/(n^2))) \bigg )


\implies(1)/(n) .\frac{1}{1 +\big (  \frac  {k^2}{n^2}\big )}

We have the following theorem.

If
$f $ is integrable on [0, 1] then
$ \int _(0)^(1) f(x) dx = \lim_(n \to \infty) (1)/(n) \displaystyle \sum_(r = 1)^(n) f( (x)/(n))    $
.

Now, let
$ (k)/(n) = x $


$ \implies dx = (1)/(n) $.

Therefore the summation becomes


$ = \int_(0)^(1) \bigg ( (1)/(1 + x^2) \bigg )


$ \implies \tan^(-1)(x)|_(0)^(1) $


$ \implies tan^(-1)(1) - tan^(-1)(0) $


$ = (\pi)/(4)  - 0 $


$ = (\pi)/(4) $

Hence, the sum is
$ \pi $/4
.

User Priyan RockZ
by
6.4k points